Constructing Paul - Johnson, Luke Timothy 1943- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2020)
"First of a two-volume work providing a framework for understanding the life and thought of the apostle Paul"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc